2020
DOI: 10.1002/adsc.201901389
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalysed Dehydrogenative Coupling – An Overview

Abstract: Manganese‐catalysed reactions have attracted great attention recently due to the high relative abundance and cheap and eco‐friendly behaviour. Applications of manganese catalysis in cross‐dehydrogenative coupling are among the hottest areas since 90% of the contributions are very recent. Dehydrogenation of alcohols using Mn‐pincer systems is highly explored nowadays for cross‐coupling to synthesise a variety of products and Mn‐catalysed C−H activation, and radical reactions are applied in dehydrogenative coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 100 publications
(99 reference statements)
0
41
0
Order By: Relevance
“…Shaikh et al demonstrated an efficient protocol for C(sp 3 )À H alkynylation of 4-thiazolidinone with terminal alkynes using Cu as catalyst via cross-dehydrogenative coupling reaction. [29] The strategy involves the C(sp 3 )À C(sp) oxidative coupling of various 4-thiazolidines (17) with different terminal alkynes (18) using 10 mol% CuBr in DCE using TBHP as oxidant in air at 90°C (Scheme 5). The 4-thiazolidinone containing both electrondeficient and electron-rich groups showed good tolerance.…”
Section: Alkynylation or C(sp 3 )à C(sp) Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaikh et al demonstrated an efficient protocol for C(sp 3 )À H alkynylation of 4-thiazolidinone with terminal alkynes using Cu as catalyst via cross-dehydrogenative coupling reaction. [29] The strategy involves the C(sp 3 )À C(sp) oxidative coupling of various 4-thiazolidines (17) with different terminal alkynes (18) using 10 mol% CuBr in DCE using TBHP as oxidant in air at 90°C (Scheme 5). The 4-thiazolidinone containing both electrondeficient and electron-rich groups showed good tolerance.…”
Section: Alkynylation or C(sp 3 )à C(sp) Bond Formationmentioning
confidence: 99%
“…Cross-dehydrogenative coupling (CDC) is an emerging subclass of CÀ H functionalization and is the most attractive strategy for the construction of CÀ C or CÀ X bonds by the coupling of unactivated CÀ H bonds bearing organic moieties under oxidative condition through the effective loss of two hydrogen atoms. [17][18][19][20][21][22][23][24] Nowadays copper has received great attention in CDC reaction and is one of the hottest research areas in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the most promising results in sustainable transformations have been achieved with second and third-row transition metals, such as Ru [40,[64][65][66][67][68][69][70][71][72], Os [73][74][75][76], Ir [77][78][79][80][81], Rh [82,83], and Pd [84][85][86][87][88][89]. Nevertheless, the current trend in the scientific community is to identify cheaper alternatives based on earth-abundant metals such as Fe [90][91][92][93][94][95][96], Mn [97][98][99][100], Ni [101][102][103][104][105], V [106][107][108], and Co [109][110][111]…”
Section: Introductionmentioning
confidence: 99%
“…Manganese is one of the most abundant and nontoxic transition metals found in the earth's crust and its corresponding complexes and salts are useful in synthetic organic reactions [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Highly reactive and selective bromination reactions have been achieved using a stoichiometric amount of MnO 2 [44] or a catalytic amount of Li 2 MnO 3 [45] under fluorescent light irradiation in the presence of Br 2 (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%